Simple Switching Strategy for High-Torque Control Performance utilizing Neutral Point Clamped Multilevel Inverter - Nor Faezah Alias; Auzani Jidin; Atikah Razi; Tole Sutikno; Huzainirah Ismail (Institute of Advanced Engineering and Science, 2013)
Three-level Neutral Point Clamped (NPC) inverter allows the configuration of switching devices to operate at high voltage and produce lower current/voltage harmonics. It is known that, DTC of induction machine which employs hysteresis controller has major drawbacks namely larger torque ripple and variable switching frequency. This paper aims to propose a suitable voltage vector selection to provide better torque regulation and lower switching frequency by employing DTC with 3-level NPC multilevel inverter. A simple switching strategy was formulated using 7-level torque hysteresis and 2-level flux hysteresis controllers to give more options in selecting an appropriate voltage vector, inherently, according the motor operation conditions. The improvements offered were verified through simulations.DOI: http://dx.doi.org/10.11591/ijpeds.v3i4.5248